2012
DOI: 10.1371/journal.pone.0046278
|View full text |Cite
|
Sign up to set email alerts
|

A New Slow Releasing, H2S Generating Compound, GYY4137 Relaxes Spontaneous and Oxytocin-Stimulated Contractions of Human and Rat Pregnant Myometrium

Abstract: Better tocolytics are required to help prevent preterm labour. The gaseotransmitter Hydrogen sulphide (H2S) has been shown to reduce myometrial contractility and thus is of potential interest. However previous studies used NaHS, which is toxic and releases H2S as a non-physiological bolus and thus alternative H2S donors are sought. GYY4137 has been developed to slowly release H2S and hence better reflect endogenous physiological release. We have examined its effects on spontaneous and oxytocin-stimulated contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 71 publications
(108 reference statements)
2
32
0
Order By: Relevance
“…For example, Johansen et al (2006) were the first to show that NaSH limited infarct size in a rat isolated heart preparation, while Pan et al (2009) Chuah et al (2007) reported that allitridum and S-allylcysteine respectively also elicited cardioprotection against myocardial infarction when given before ischemia. Preconditioning the heart with the thiol derivative S-diclofenac was also protective partially through the opening of mitochondrial K ATP channels (Rossoni et al, 2008). Investigators also have examined the possibility of postconditioning the myocardium using NaSH and Na 2 S.…”
Section: Infarct Limitation By Gyy4137mentioning
confidence: 99%
“…For example, Johansen et al (2006) were the first to show that NaSH limited infarct size in a rat isolated heart preparation, while Pan et al (2009) Chuah et al (2007) reported that allitridum and S-allylcysteine respectively also elicited cardioprotection against myocardial infarction when given before ischemia. Preconditioning the heart with the thiol derivative S-diclofenac was also protective partially through the opening of mitochondrial K ATP channels (Rossoni et al, 2008). Investigators also have examined the possibility of postconditioning the myocardium using NaSH and Na 2 S.…”
Section: Infarct Limitation By Gyy4137mentioning
confidence: 99%
“…Products of this H2S/NO interaction appear to have pronounced biological effects; however the nature of the reaction intermediates is currently unclear and many inconsistencies remain; for example, H2S donors were found to either potentiate or attenuate relaxation effect of NO donors in isolated aortic rings in vitro [15,16], or result in complete loss of vasodepressor activity in anesthetized rats [16]. H2S was shown to relax uterus from pregnant [17,18] and non-pregnant rats [19], and sodium nitroprusside (SNP) prevented H2S induced relaxation of rat uterus [20]. Thionitrous acid (HSNO) has been proposed to represent an important carrier of bioactivity of the interaction of S-nitrosothiols with H2S [10], but the evidence provided appears to be inconsistent with the known chemical properties of HSNO.…”
Section: Introductionmentioning
confidence: 99%
“…A similar smooth muscle relaxant effect of GYY4137 has now been described in a range of tissues including human airway smooth muscle cells via opening of sarcolemma K ATP channels (Fitzgerald et al, 2014), mouse intrapulmonary airways by an effect on intracellular calcium release (Castro-Piedras & Perez-Zoghbi, 2013), pig bladder neck tissues again by opening K ATP channels (Fernandes et al, 2013), pregnant rat myometrial smooth muscle cells (Robinson & Wray, 2012) and in the bovine ciliary artery (Chitnis et al, 2013). Intriguingly, GYY4137 can occasionally, and in defined conditions, exert the opposite effect on blood vessels.…”
Section: Effect Of Gyy4137 On Nonvascular Smooth Musclementioning
confidence: 55%